Aplikasi HIMAINFRA Berbasis Android - Silvy Krismayanti Winarto Giam; Henry Novianus Palit; Anita Nathania Purbowo (Jurnal Infra, 2018)
HIMA or Himpunan Mahasiswa is a student union on the department’s level in a university. HIMAINFRA is the Student Union of the Department of Informatics and Business Information System of Petra Christian University. HIMAINFRA aims to address the needs of all students of the Department of Informatics and Business Information System of Petra Christian University in academic and non academic matters. One of the services of HIMAINFRA is to distribute announcements and upcoming events to the students.Nowadays, HIMAINFRA uses posters and social media, such as LINE and Instagram, to distribute the announcements and information to the students. However, due to some limitations on the social media, not all announcements and information from HIMAINFRA can be received by the students. Besides that, to register as an event participant or an event committee, the student still need to do it manually (i.e., paper-based).This Android-based HIMAINFRA application was developed to help HIMAINFRA distribute the announcements and information. This application also helps HIMAINFRA’s members on running a committee and enables the students of the Department of Informatics and Business Information System to register online as event participants or committees. This application leverages on Firebase Realtime Database and Firebase Cloud Messaging.